ETNOGRAFI KOMUNIKASI DALAM PROSESI UPACARA ADAT BATAGAK GALA PANGULU SUKU CANIAGO DI NAGARI CUPAK KECAMATAN GUNUNG TALANG KABUPATEN SOLOK - Qolby, Aqsha Qhairatul; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
Batagak gala penghulu traditional ceremony is a ceremony carried out by the caniago tribe in Nagari Cupak, Gunung Talang District, Solok Regency. The purpose of this study was to determine the communicative situation, communicative events and communicative acts in the procession of Batagak gala pangulu traditional ceremony of caniago tribe in Nagari Cupak, Gunung Talang District, Solok Regency. The research used qualitative methods. The research subjects were 4 people who were traditional leaders, 1 bundo kandung, 2 urang pangka and 1 anak pisang who were selected using purposive techniques. The results showed that first, the communicative situation was carried out in the gadang house. Second, communicative events include all the series that make up communication, starting from the type of event, topic, purpose and function, participants, message form, message content, action sequence, interaction rules and interpretation norms and the last communicative act is a person who understands and knows the implementation of traditional ceremony.